The larvae of Sericostoma sasbaddes Malicky 2010, S. maclachlanianum Costa 1884, S. clypeatum Hagen 1864, and S. siculum McLachlan 1876 (Trichoptera: Sericostomatidae), including a preliminary key to the Sericostomatidae larvae of European Ecoregion 3 (Italy, Corsica, and Malta) - Waringer, Johann; Malicky, Hans (Zootaxa, 2018)
Caddisfly samples collected from Corsica, Sardinia, and the Italian mainland included the adults of Sericostoma sasbaddes Malicky 2010, S. maclachlanianum Costa 1884, S. clypeatum Hagen 1864, and S. siculum McLachlan 1876. This material, combined with the unique distribution patterns of the four species, enabled the association of the final instar Sericostoma larvae collected at the same locations. Larvae of the two species from Sardinia (S. sasbaddes, S. maclachlanianum) can be separated by the number of bifurcate setae on each pleuron VIII. The two other species are geographically well separated: S. clypeatum is the only Sericostoma species present in Corsica, whereas S. siculum is confined to the Southern Italian Provinces including Sicily. Morphological characters from the larval descriptions have been used for constructing a preliminary larval key to the hitherto known Sericostomatidae species from European Ecoregion 3 (Italy, Corsica, and Malta).